EKONOMI POLITIK MEDIA: PADA PEMBERITAAN MENJELANG PEMILIHAN GUBERNUR BANTEN 2017 OLEH RADAR BANTEN DAN BARAYA TV - P, Achmad Nashrudin (Universitas Negeri Yogyakarta, 2016)
Research on Political Economy of Media: At the news ahead of elections for the governor of Banten in 2017 by Radar Banten and Baraya TV, phenomenon triggered by the loosening of the values of objectivity and independence of the mass media in carrying out its functions as set in the Press Law and the Broadcasting Law. At the time of the campaign, the candidates for governor and lieutenant governor are competing to get the